INFLUENCE OF ORGANIZATIONAL CULTURE ON CORPORATE BRAND - N. A. Bashkina; N. V. Klym-Eremina; V. V. Orlov (Вестник университета, 2020)
Brand, being a significant intangible resource, requires special attention not only from marketers, but also from the management of the organization, as its formation affects various aspects of production and economic activity. The given review of the Russian and foreign points of view on interrelation of organizational culture of corporation and its brand, allows us to make a conclusion about necessity of further in-depth studying of this issue. The mutual influence of the organizational culture of the corporation and its brand at the deep level has been revealed and substantiated in the article. The study results of the influence of the organizational culture main components such as corporate culture, corporate social responsibility, on the corporation brand, – have been reflected. Special attention has been paid to the effective interaction with the media, which are a brand guide for the target audience.